Checks, balances, and appointments in the public service: Israeli experience in comparative perspective - Amado, Rivka (2001)
This article explores the process of appointing government ministers and senior executive officials in Israel. It provides several case studies of the appointment process in the 1990s, a period of hyperfragmentation in the Israeli parliament. These studies reveal evidence of gross irresponsibility in the appointment process, as well as a lack of a meaningful oversight and checks in the process. One consequence is that the Israeli High Court was asked to intervene and review and reject a number of these appointments. The article argues that although well meaning, this intervention represents a dangerous new trend; this new role for the Courts is both inappropriate and counterproductive. It is inappropriate because judicial intervention imposes a legal solution when a political solution is called for, and it is counterproductive because frequent judicial intervention weakens both the judiciary and the political process. The article concludes with a proposal for an alternative approach to cope with the lack of meaningful oversight in the political-appointment process. - Reproduced
Keywords: Civil service - Israel; Civil service